The effect of character-charged maritime textbooks on increasing students’ character values - Nuraeni Nuraeni; Sarilah Sarilah; Gunarti Dwi Lestari; Wiwin Yulianingsih; Muhammad Tahir (International Journal of Evaluation and Research in Education (IJERE), 2024)
Teaching and learning activities for early childhood students currently do not support increasing the character values of graduates, and the emphasis is still on learning whose output leads to competency according to standards. Using character-charged maritime textbooks is a solution to assist teachers in facilitating the application of character values in marine learning. The purpose of this research is to evaluate the impact of character-focused marine textbooks on students’ moral development. The method of research is quasi-experimental, with a pretest-posttest design. The sampling technique is convenience sampling. Two classes use the method, B1 for experimental purposes (with 80 students) and B2 for comparison (with 80 students). Independent T-tests were used in data analysis to compare differences in students’ average scores in the experimental and control groups before the intervention. N-Gain was used to compare the character growth of control and intervention students. The study’s findings indicate that students’ character values significantly influence adoption of morally edifying maritime textbooks. This shows increased student character values, namely responsibility, honesty, discipline, love and affection, caring, courage, independence, and hard work, after being taught using character-charged maritime textbooks. Thus, it can be concluded that character-charged maritime textbooks can significantly increase students’ character values.